2014
DOI: 10.1186/s12916-014-0165-7
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-visit variability of fasting plasma glucose as predictor of ischemic stroke: competing risk analysis in a national cohort of Taiwan Diabetes Study

Abstract: BackgroundGlycemic variation as an independent predictor of ischemic stroke in type 2 diabetic patients remains unclear. This study examined visit-to-visit variations in fasting plasma glucose (FPG), as represented by the coefficient of variation (CV), for predicting ischemic stroke independently, regardless of glycated hemoglobin (HbA1c) and other conventional risk factors in such patients.MethodsType 2 diabetic patients enrolled in the National Diabetes Care Management Program, ≥30 years old and free of isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 44 publications
(48 reference statements)
3
62
0
1
Order By: Relevance
“…Recent studies and a systematic review have shown that glycemic variability might play an important role in the pathogenesis of atherosclerosis, and may be an independent risk factor for ischemic stroke8 and all‐cause mortality in those with type 2 diabetes mellitus 9, 10. However, these previous studies on glycemic variability were all short‐term within 1 year or less and investigated in patients with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies and a systematic review have shown that glycemic variability might play an important role in the pathogenesis of atherosclerosis, and may be an independent risk factor for ischemic stroke8 and all‐cause mortality in those with type 2 diabetes mellitus 9, 10. However, these previous studies on glycemic variability were all short‐term within 1 year or less and investigated in patients with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…The patients were grouped into four quartiles according to FPG-CV measurements. 19 The results revealed that compared to patients with the first quartile, higher associated risk of developing ischemic stroke in patients who fell into second, third, and fourth FPG-CV quartile, independent of HbA1c level.…”
Section: 18mentioning
confidence: 88%
“…However, in the Taiwan Diabetes Study, FPG-CV still showed links with incidence of ischemic stroke after excluding patients with hypoglycemia in sensitivity analysis; this association cannot be explained by hypoglycemia in patients with high glucose variability. 19 Further studies need to investigate the effects of glycemic variability whether co-existence of hypoglycemia or not for diabetic complications.…”
Section: Glycemic Variability and Hypoglycemia Complica-tionsmentioning
confidence: 99%
“…Thus, FPG might be a sensitive indicator for capturing variation of glucose due to overindulgence in diet given that HbA 1c is a mean over the previous 3 months prior to the measurement. Visit-tovisit FPG-CV as a marker for glucose variability has provided longer observation spectrum and good prediction power to further survival [15,16], cardiovascular events [15], stroke [17], and DM nephropathy [18]. Previous studies suggested type 2 diabetes was associated with increased risk of hip fracture [5].…”
Section: Discussionmentioning
confidence: 98%